Peran Orang Tua Dalam Perkembangan Sosial Motorik Anak-Anak Attention Deficit Hyperactivity Disorder - Junaidin, Junaidin (LP2M Universitas Islam Ahmad Dahlan, 2024)
This study aims to analyze the social motor development in children with Attention Deficit Hyperactivity Disorder using a qualitative approach. To collect data, besides direct observation for 7 consecutive days, the researcher also conducted interviews and used the ADHD checklist proposed by DuPaul, G.J. This form emphasizes the following aspects: 1) Attention and Focus, 2) Hyperactivity, 3) Impulsivity, 4) Social Relationships. The results of this study indicate that children with Attention Deficit Hyperactivity Disorder (ADHD) aged 4-16 years in the Bima district fall into the category of very concerning for their social motor development. About 90.9% have difficulty remaining calm, and 72.7% tend to exhibit impulsive and hyperactive behaviors, which often lead to being ostracized by their playmates. The role of parents as educators and protectors is crucial to control their child's impulsive and hyperactive behaviors, thereby reducing the psychological impact of social marginalization.